Study of flow over dimpled cylinder - Tan, Shu Pei (2014)
Drag reduction of flow over a circular cylinder is done through by having a dimpled surface. Computational fluid dynamics (CFD) simulations are done to investigate the degree of drag reduction by dimpled cylinder as compared to smooth cylinder and the results are to be validated by wind tunnel experimentations.